Design of 3D printed pressure-reducing insoles based on changes in parameters of lattice structure - Lu-Ping Kang; Tai-Sheng Gong (Advances in Mechanical Engineering, 2023)
Uneven distribution of pressure on the bottom of the foot or excessive local pressure shall cause discomfort. And when it gets severe, this pressure would even damage the health of the human foot, especially for people like the elderly, diabetic patients and pregnant women. Decompression footwear can effectively reduce pressure on the foot and reduce the risk of injury. However, mass-produced pressure-reducing footwear lacks pertinence due to individual differences in human plantar pressure and foot shape data. This paper presents a design, using gradient lattice structures, for four kinds of 3D printed pressure-reducing insoles. It turns out that full contact insoles with non-uniform distribution of lattice structure did the best in reducing peak pressure of the whole foot, which was 60.42% lower than that of bare foot, 17.24% of flat insole with uniform distribution of lattice structure, 13.68% of mass-produced pressure-reducing footwear. The effect on pressure reduction is significant.